Diverging playing positions do not lead to differences in YBT-UQ performance in youth handball players - Bauer, J.; Schwiertz, G.; Muehlbauer, T. (Sports Medicine International Open, 2021)
Handball playing positions can be differentiated between first line players who position themselves near the 6-m line and second line players who typically play outside the 9-m space. Handball is characterized by a high number of throwing actions that cause adaptations in the throwing shoulder. The objective of this cross-sectional study was to assess whether the specific physiological positional demands in handball lead to functional performance differences between the playing positions (N=196; goalkeepers: n=25; backcourt: n=99; pivots: n=21; winger: n=51) in terms of shoulder mobility and stability in any reach direction as assessed through the Upper Quarter Y Balance Test (YBT-UQ). Contrary to our hypothesis, the results did not show significant differences between the playing positions in shoulder mobility and stability in youth handball players, irrespective of reach arm and reach direction. The obtained effect sizes (? p 2) were solely small and ranged between 0.01 and 0.03. The adaptations following the demands of the diverging playing positions do not lead to significant differences in shoulder mobility and stability on the basis of the YBT-UQ. The overall training load of youth handball players may not be sufficient to lead to significant position-specific differences in shoulder mobility and stability.